Aging, Mitochondria and Male Reproductive Function - Amaral, Sandra; Ramalho-Santos, Joao (Current Aging Science, 2009)
The rise in life expectancy over the last century, together with higher maternal and paternal ages and have highlighted the issue of reduced fertility with advancing age. Aging of the male reproductive system is incited by multifactorial changes at molecular, cellular and regulatory levels, and individual characteristics are highly variable, although strongly influenced by lifestyle and environmental factors. Damage accumulated with age leads to progressive deregulation of the hypothalamic-pituitary-gonadal axis and of local auto/paracrine interactions, thereby inducing changes in target organs such as the testis, penis and prostate. Elderly human males produce less testosterone, have fewer motile sperm and a higher incidence of erectile dysfunction and prostate disorders, all of which contribute to lower fertility. Cellular aging can manifest itself at several levels. Aging cells progressively accumulate “waste” products, resulting in a decreased functionally. Changes to mitochondria are among the most remarkable features observed in aging cells and several theories place mitochondria at the hub of cellular events related to aging, namely in terms of the accumulation of oxidative damage to cells and tissues, a process in which these organelles may play a prominent role, although alternative theories have also emerged. Furthermore, mitochondrial energy metabolism is also crucial for male reproductive function and mitochondria may therefore constitute a common link between aging and fertility loss.
Keywords: mitochondria